EMOSI PELANGGAN: ANTESENDEN DAN KONSEKUENSI - Ken Sudarti (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2013)
This article explains how important the role of customer emotions on consumer behavior andits influencing variables. During this time, the role of emotion is not so much revealed, but thedecision-making without the role of emotions is not possible. There are many variables thataffect and are affected by customer emotions, but in this article only described about serviceenvironment and employees behavior as an antecendence variables and complaints behavior,customer satisfaction and customer loyalty as a consequence variables. Employee behavior isinfluenced by the environment service itself, the mood of the team work and the emotions of the employee.